Post-stroke mortality in ICU patients with serum glucose-potassium ratio: an analysis of MIMIC-IV database - Yuan, Zhen; Chen, Aoli; Zeng, Yunqing; Cheng, Jiwei (Frontiers in Neurology, 2025)
IntroductionAcute ischemic stroke (AIS) patients admitted to the intensive care unit (ICU) have a high mortality rate, necessitating the early identification of those at risk of a poor prognosis. This study investigated the association between the blood glucose-to-potassium ratio (GPR) and the prognosis of AIS patients.MethodsWe conducted a retrospective cohort study using data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The primary outcomes were 28-day, 90-day, and 1-year mortality rates following ICU admission. Multivariate Cox proportional hazards regression models were used to estimate adjusted hazard ratios (HRs) with 95% confidence intervals (CIs). Subgroup analyses, Kaplan–Meier survival curves, and restricted cubic spline models were employed to further evaluate the relationship between the GPR and mortality in AIS patients.ResultsA total of 2,636 AIS patients were included in the study, with a mean age of 69.4 ± 15.6 years. The 1-year mortality rate was 36.8% (n = 969). After adjusting for confounders, compared with the first quartile (Q1, GPR ≤ 1.39), the 1-year mortality risks for the second quartile (Q2, 1.39 < GPR ≤ 1.74), third quartile (Q3, 1.74 < GPR ≤ 2.25), and fourth quartile (Q4, GPR ≥ 2.25) were HR = 1.17 (95% CI: 0.95–1.43, p = 0.132), HR = 1.42 (95% CI: 1.17–1.73, p < 0.001), and HR = 1.61 (95% CI: 1.33–1.96, p < 0.001), respectively. Similar trends were observed for 28-day and 90-day mortality. Kaplan–Meier (KM) analysis revealed that groups with higher GPRs had higher mortality rates at 28 days, 90 days, and 1 year. Non-linear analysis further confirmed the presence of an inflection point in the association between the GPR and 365-day mortality, which was identified at GPR = 2.75. At ratios less than this threshold, the risk of mortality increased significantly with increasing GPR (HR: 1.466; 95% CI: 1.239–1.735; p < 0.001). However, above this ratio, the association plateaued and was no longer statistically significant (HR: 0.899; 95% CI: 0.726–1.113; p = 0.095).ConclusionThe GPR is an independent predictor of poor prognosis in AIS patients admitted to the ICU. Higher GPRs are associated with increased 28-day and 90-day mortality rates, highlighting the potential utility of this ratio in risk stratification and clinical decision-making. A non-linear relationship was observed between the GPR and 365-day mortality, with an inflection point identified at GPR = 2.75.